The Secrets of Freemasonry : Revealing the Suppressed Tradition - Lomas, Robert (London Constable & Robinson Ltd., 2006)
Many people are curious about the existence of secret societies which claim to hold arcane religious or esoteric knowledge and pass it down through the generations via selected adepts. Classic Masonic writers including William Preston, Robert Gould, JSM Ward, AE Waite and WL Wilmshurst have written about secret traditions connected to the Temple of Sion. Each has different ideas about how mystical knowledge came into Freemasonry. Some say that the Charter of Larmenius reveals an underground line of Knight Templar Grand Masters who survived down to the nineteenth century. All agree there is a Secret Lodge or House of Adepts who continue to teach "true" knowledge of the ancient mysteries and that The Craft transmits beliefs linked to the Earls of Rosslyn, the Knights Templar, and Lodge Mother Kilwinning. Masonic expert Robert Lomas has collected together this thread of belief from old Masonic writers and rewritten it in modern English to make the ideas accessible to modern readers.
Include Appendix and Bibliography.
Inside the hidden world of Masonic lore and symbolism.
Keywords: Freemasonry -- Freemasonry--Rituals